1993
DOI: 10.1007/bf01973643
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis caused byNeisseria elongata subspeciesnitroreducens: Case report and literature review

Abstract: Neisseria elongata subsp. nitroreducens, an usual commensal of the nasopharynx, can cause serious infections, usually endocarditis. A case of Neisseria elongata endocarditis complicating mitral valve prolapse in a patient allergic to penicillin is reported. Cure was obtained with a combination of ceftriaxone and gentamicin, there being no requirement for surgery during the acute phase of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…It is of interest that five patients had identified; however, including ours, only 11 cases (four females and seven males) met the Duke criteria (table 1). Including our progressive disease while receiving appropriate antibiotic therapy and required valve replacement [1,[4][5][6][7]. Despite its severity, no patient, there were seven cases of definite infective endocarditis [1,[4][5][6][7] and four cases of possible infective endocarditis [3, 8-deaths associated with this illness have been reported.…”
Section: Nitroreducens: Case Report and Reviewmentioning
confidence: 99%
“…It is of interest that five patients had identified; however, including ours, only 11 cases (four females and seven males) met the Duke criteria (table 1). Including our progressive disease while receiving appropriate antibiotic therapy and required valve replacement [1,[4][5][6][7]. Despite its severity, no patient, there were seven cases of definite infective endocarditis [1,[4][5][6][7] and four cases of possible infective endocarditis [3, 8-deaths associated with this illness have been reported.…”
Section: Nitroreducens: Case Report and Reviewmentioning
confidence: 99%
“…nitroreducens appears uniformly susceptible to most antibiotics including ampicillin [1]. T h e course of the endocarditis was always favourable in patients on antibiotic therapy, eventually followed by valve replacement [4,8]. Antibiotic therapy with gentamicin for 14 days and ampicillin for 6 weeks also cured the endocarditis of our patient without serious cardiac valve damage.…”
Section: Discussionmentioning
confidence: 93%
“…O f these 12 bacteremic strains, nine (75 % ) were associated with the clinical diagnosis of endocarditis. T o our knowledge, only seven other cases have b e e n described in detail in the English literature [3,4,[7][8][9]11]. W h e n blood cultures are positive for N. elongata, endocarditis should be sought systematically.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A few cases of IE caused by N. elongata subsp nitroreducens have been described. 2,8,9 In 1990, on the basis of biochemical and DNA studies, the Centers for Disease Control reported on the analysis of 95 strains that belonged to the genus Neisseria and recognized that N. elongata subsp nitroreducens was an important pathogen of the genus Neisseria and was responsible for significant infections, such as septicemia, in human beings. In recent decades, the chief designation of this organism as a cause of IE-induced septicemia has been non-gonococcal, non-meningococcal Neisseriae.…”
Section: Discussionmentioning
confidence: 99%